Food safety regulatory systems in Europe and China: A study of how co-regulation can improve regulatory effectiveness - Chen, Kevin Z.; Wang, Xin-xin; Song, Hai-ying (Elsevier, 2015)
Food safety has received a great deal of attention in both developed and developing countries in recent years. In China, the numerous food scandals and scares that have struck over the past decade have spurred significant food safety regulatory reform, which has been increasingly oriented towards the public-private partnership model adopted by the Europe Union's (EU) food safety regulatory system. This paper analyzes the development of both the EU's and China's food safety regulatory systems, identifies the current challenges for China and additionally considers the role of public-private partnership. The success of co-regulation in the food regulatory system would bring significant benefits and opportunities for China. Finally, this paper recommends additional measures like training and grants to improve the private's sector effectiveness in co-regulating China's food safety issues.